2014
DOI: 10.1136/heartjnl-2014-306068
|View full text |Cite
|
Sign up to set email alerts
|

The validation of cardiovascular risk scores for patients with type 2 diabetes mellitus

Abstract: All 10 evaluated models had a comparable and moderate discriminative ability. The recalibrated, but not the original, prediction models provided accurate risk estimates. These models can assist clinicians in identifying type 2 diabetes patients who are at low or high risk of developing CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 33 publications
3
38
1
2
Order By: Relevance
“…The c ‐statistic in the current study was larger than typically observed with CV prediction models for T2DM at 0.782, possibly explained by a diabetic cohort both with and without known cardiac conditions at baseline, and consideration of an endpoint more amenable to prediction (HF, rather than MI or ischemic stroke) . Not surprisingly, multiple CV‐related phenotypes (CAD, atrial fibrillation), traditional CV risk factors (age, systolic blood pressure, smoking), and markers of kidney dysfunction (blood urea nitrogen, albumin) were independent predictors of HHF.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The c ‐statistic in the current study was larger than typically observed with CV prediction models for T2DM at 0.782, possibly explained by a diabetic cohort both with and without known cardiac conditions at baseline, and consideration of an endpoint more amenable to prediction (HF, rather than MI or ischemic stroke) . Not surprisingly, multiple CV‐related phenotypes (CAD, atrial fibrillation), traditional CV risk factors (age, systolic blood pressure, smoking), and markers of kidney dysfunction (blood urea nitrogen, albumin) were independent predictors of HHF.…”
Section: Discussioncontrasting
confidence: 55%
“…Though T2DM is strongly associated with a broad range of CV outcomes, and several prediction models exist for predicting CV risk in T2DM, multiple arguments can be put forth for creating a prediction model specifically for HHF. 20,21 First, an HHF is typically associated with an exacerbation of an underlying cardiac disorder, distressing symptoms, and portends an increased risk of short-term mortality; thus, HHF is a serious health event warranting preventive focus. 14,22 Furthermore, T2DM is frequent among patients with an HHF, with up to 44% of hospital admissions related to HF reporting comorbid diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic activity is essential for life, and metabolic disorders have been found to be associated with many diseases including CHD [8]. Many serum biochemical indices, which reflect dynamic physiological and pathophysiological processes within the body, have been found to be associated with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Also it should be noted that existing prediction models for patients with type 2 diabetes mellitus are known to perform generally moderate, even after recalibration. 46 Moreover, it was recently shown that ARRs estimated with models that are internally developed in trial data result in limited bias compared with predictions based on existing external risk scores, given that the number of events per predictor does not exceed 10. 6 Also the fact that the newly developed model performs well in 2 external validation sets in which the patients differ considerably in baseline characteristics (Table 1) as well as in an observational cohort of patients with type 2 diabetes mellitus ( Figure I in the Data Supplement) is reassuring for the generalizability of this model to a broad range of patients with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%